Estimativas de mortalidade adulta em Moçambique, 1987 a 2007 - Serafim Adriano Alberto (2013)
Mortality estimates are important for understanding population dynamics, changing health status of a population and improve the planning of the country. However, in many developing countries, as is the case of Mozambique, the poor quality or lack of information on deaths precludes the production of mortality estimates. This study aims to evaluate the quality of population and mortality data and produce estimates of adult mortality in Mozambique and its regions, in periods between 1987 and 1997 and 1997 and 2007. This doctoral dissertation combines different methods of formal demography, known as Distribution Methods Deaths, with information on deaths in the household in the last twelve months to carry out the study. The application of different methodologies aims to obtain more robustmeasures of adult mortality and assess the sensitivity of the methods to countries with limited data. The results indicate that both in the country and the three regions the quality of information of deaths derived from censuses is of low quality, but has improved significantly in the intercensal period. Among regions, the best coverage of deaths was recorded in the Northern Region (0,816) and the lowest in the Central Region of the country (0,490). Estimates of adult mortality, summarized in the probability of dying between 15 and 60, indicate that both the country and regions have higher adult mortality than neighboring countries. The probability of death in 2007 was 0.593 in Mozambique compares with an average of 0.239 neighboring countries.